Mapping of Induced Effects of an Earthquake in the Region of Algiers, Algeria Using the Geographical Information System GIS. Issue 1 (November 2019) - Sadou, O.; Bourenane, H.; Louni, C.; Balla, N.; Haddouche, A.
Abstract: Landslides, rock blocks falls, liquefaction, the appearance of the surface fault and flood present the principle geological-hazard in relationship with earthquakes which will be mapped in the region of Algiers. The determination of these areas passes through a qualitative and quantitative analysis based on a recognition of the soil conditions; geological, lithological, hydro-geological, topographic, morphological and geotechnical. The assessment and mapping of the degree of induced hazard allows individualizing homogeneous areas that can behave similarly during the earthquakes.